CONSTRUCCIÓN DE ESCALAS DE ACTITUD, TIPO THURSTONE Y LIKERT - Elejabarrieta, F.; Iñiguez, L. (La Sociología en sus Escenarios, 2010)
Abstract. The scales of measurement of attitudes are a measuring instrument that allows to approach the affective variability of the people with respect to any subject, object or process. The methodology of measurement of the attitude is: A set of answers is used like indicator of an underlying variable (intervening): the attitude. The attitude constitutes an organized predisposition, for, to think, to feel, to perceive, and, to behave before a subject, object or process. A scale of attitudes is something hypothetical, that indicates to the intensity and direction of the opinion. The attitude (its affective component) is a one-dimensional variable that imagines in a continuum, that can go from “very in agreement” to very in discord”. To measure an attitude is to make an ordering of all the individuals according to are more or less favorable to a certain object. or. more generally, than they present/display in major or minor degree a certain tendency. Resumen. Las escalas de medición de actitudes son un instrumento de medición que permite acercarse a la variabilidad afectiva de las personas respecto a cualquier sujeto, objeto o proceso. La metodología de medición de la actitud es: Un conjunto de respuestas es utilizado como indicador de una variable subyacente (interviniente): la actitud. La actitud constituye una predisposición organizada, para, pensar, sentir, percibir, y, comportarse ante un sujeto, objeto o proceso. Una escala de actitudes es algo hipotético, que señala la intensidad y dirección de la opinión. La actitud (su componente afectivo) es una variable unidimensional que se representa en un continuum, que puede ir desde “muy de acuerdo” hasta muy en desacuerdo”. Medir una actitud es hacer un ordenamiento de todos los individuos según sean más o menos favorables a un cierto objeto. o. más generalmente, que presenten en mayor o menor grado una cierta tendencia.